Time to treatment and survival in veterans with lung cancer eligible for curative intent therapy. (August 2018) - Ha, Duc; Ries, Andrew L.; Montgrain, Philippe; Vaida, Florin; Sheinkman, Svetlana; Fuster, Mark M.
Abstract: Background: The Institute of Medicine emphasizes care timeliness as an important quality metric. We assessed treatment timeliness in stage I-IIIA lung cancer patients deemed eligible for curative intent therapy and analyzed the relationship between time to treatment (TTT) and timely treatment (TT) with survival. Methods: We retrospectively reviewed consecutive cases of stage I-IIIA lung cancer deemed eligible for curative intent therapy at the VA San Diego Healthcare System between 10/2010–4/2017. We defined TTT as days from chest tumor board to treatment initiation and TT using guideline recommendations. We used multivariable (MVA) Cox proportional hazards regressions for survival analyses. Results: In 177 veterans, the median TTT was 35 days (29 days for chemoradiation, 36 for surgical resection, 42 for definitive radiation). TT occurred in 33% or 77% of patients when the most or least timely guideline recommendation was used, respectively. Patient characteristics associated with longer TTT included other cancer history, high simplified comorbidity score, stage I disease, and definitive radiation treatment. In MVA, TTT and TT [HR 0.53 (95% CI 0.27, 1.01) for least timely definition] were not associated with OS in stage I-IIIA patients, or disease-free survival in subgroup analyses of 122 stage I patients [HR 1.49 (0.62, 3.59) for least timely definition]. Conclusion: Treatment was timely in 33–77% of veterans with lung cancer deemed eligible for curative intent therapy. TTT and TT were not associated with survival. The time interval between diagnosis and treatment may offer an opportunity to deliver or improve other cancer care. Highlights: The median time to curative-intent treatment was 35 days in 177 veterans. Curative-intent lung cancer treatment was not timely in 27–66% of veterans. Time-to-treatment/timely treatment was not associated with better overall survival. Time-to-treatment/timely treatment was not associated with disease-free survival.